2020
DOI: 10.4081/aiua.2020.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable bulbourethral male sling: Experience after 30 cases of moderate to severe male stress urinary incontinence

Abstract: Objective: To report our experience using the Argus perineal sling from July 2015 to April 2018 for male stress urinary incontinence (SUI) after prostatic surgery. To evaluate the safety, efficacy and healthrelated quality of life in patients undergoing this procedure. Patients and methods: The positioning of an adjustable bulbourethral male sling provides a perineal incision, exposure of the bulbospongiosus muscle and the application of the sling bearing on it with transobturator passage of the two extremitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…36,37 Similarly, in the RP setting for PC, several well-established patient disease-specific, psychological as well as pathological features may condition UI after RP. 38,39 Unfortunately, these variables were not addressed or not adequately classified by all the selected studies as data regarding pre-operative conditions, co-morbidities, prostate volume and surgical techniques used to reduce the incidence of post-RP UI are incomplete. All these variables likely conditioned the heterogeneity of UI levels detected in terms of pad weight at baseline after catheter removal.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Similarly, in the RP setting for PC, several well-established patient disease-specific, psychological as well as pathological features may condition UI after RP. 38,39 Unfortunately, these variables were not addressed or not adequately classified by all the selected studies as data regarding pre-operative conditions, co-morbidities, prostate volume and surgical techniques used to reduce the incidence of post-RP UI are incomplete. All these variables likely conditioned the heterogeneity of UI levels detected in terms of pad weight at baseline after catheter removal.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] However, complications such as sling erosion or infection are not uncommon and the device explantation rate remains quite high (up to 16%). [11][12][13][14][15] Remeex sling (Neomedic, Barcelona, Spain) Manufacturer and device specifications. The Remeex sling, also known as the REadjustable MEchanical EXternal device, is manufactured by Neomedic in 2004.…”
Section: Surgical Techniques and Clinical Outcomesmentioning
confidence: 99%
“…In looking at the Argus sling, Cotugno et al reported a short-term study at 3 months post-operation that 70% (21 patients) reached total continence defined as using less than one PPD (58). The remaining 30% (9 patients) were noted as having a clinically significant improvement (58).…”
Section: The Adjustable Slingmentioning
confidence: 99%
“…In looking at the Argus sling, Cotugno et al reported a short-term study at 3 months post-operation that 70% (21 patients) reached total continence defined as using less than one PPD (58). The remaining 30% (9 patients) were noted as having a clinically significant improvement (58). Looking at differences in outcome due to preoperative conditions, Bochove-Overgaauw et al reported differences of 92% (12 of 13), 67% (29 of 43), and 67% (26 of 39) in the mild, moderate, and severe incontinence group (59).…”
Section: The Adjustable Slingmentioning
confidence: 99%